1995
DOI: 10.1159/000133926
|View full text |Cite
|
Sign up to set email alerts
|

Fine deletion mapping of the p22 region of the human X chromosome using a radiation-induced hybrid panel

Abstract: Radiation-induced somatic cell hybrids containing fragments of the human X chromosome were constructed. A panel of 17 hybrids was selected with the help of known markers in the Xp22 region. These hybrids identified 11 different breakpoints between Xp22.2 and Xp21.3. Eight markers were located in eight of the nine corresponding intervals, resulting in the following physical map: tel DXS89-DXS278-DXS85-(DXS1224, DXS16)-(GLRA2, DXS987)-DXS207-(DXS-197, DXS1053)-(DXS43, DXS1195)-(DXS1229, DXS-999)-(DXS1052, DXS92,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1995
1995
1995
1995

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…The following integrated map is proposed (Heuertz et al 1995 Cross overs in the SEDL families helped to refine the order of several markers (Table 1). The analysis was based on the assumption that only one crossover had occurred: we showed that DXS143 is distal to DXS 1043, which is itself distal to DXS85.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The following integrated map is proposed (Heuertz et al 1995 Cross overs in the SEDL families helped to refine the order of several markers (Table 1). The analysis was based on the assumption that only one crossover had occurred: we showed that DXS143 is distal to DXS 1043, which is itself distal to DXS85.…”
Section: Resultsmentioning
confidence: 99%
“…To refine this localization further, we have rescreened 14 of our original families and one further family, with newly identified microsatellite markers (Gyapay et al 1994). Initially, we integrated the previous RFLP map with that of Genethon, by using a panel of radiation induced hybrids (Heuertz et al 1995). The subsequent analysis of current linkage data using these markers and a consideration of previously published data enabled a substantial refinement of the genetic map.…”
Section: Introductionmentioning
confidence: 99%